Host-induced gene silencing targeting the calcineurin of Fusarium fujikuroi to enhance resistance against rice bakanae disease - Hou, Yi-Hsuan; Zhang, Ting-Xiang; Chen, Ying-Lien (Frontiers in Plant Science, 2025)
Bakanae, or foolish seedling disease of rice, is caused by the ascomycetous fungus Fusarium fujikuroi, which is prevalent in many rice-growing countries. Current protection strategies depend on fungicides, but this results in chemical-resistant F. fujikuroi and detrimental environmental effects. It is known that calcineurin controls Ca2+ signaling, which mediates growth, stress responses, and pathogenicity in fungi. Based on the pharmacological inhibition of calcineurin in F. fujikuroi, we discovered that calcineurin inhibitor FK506 or cyclosporin A can intensely prevent the growth of F. fujikuroi, and further investigated the feasibility of silencing calcineurin genes of F. fujikuroi in rice using host-induced gene silencing (HIGS) to confer resistance to bakanae disease. The constructs FfCNA1-Ri and FfCNB1-Ri were introduced into rice plants by using Agrobacterium-mediated gene transformation, and the copy numbers of transgenes were examined by Southern blot hybridization in the transgenic lines. The results of pathogen inoculation assay and fungal biomass quantification demonstrated that the transgenic rice plants that carry the FfCNA1-Ri or FfCNB1-Ri construct had increased resistance against bakanae disease. We propose that RNAi-derived siRNAs might efficiently suppress the expression of calcineurin genes in F. fujikuroi, leading to impaired growth and poor colonization of F. fujikuroi in rice. These findings indicate that HIGS might be a potential disease management strategy for rice bakanae disease.